Selectivity of the botanical compounds to the pollinators Apis mellifera and Trigona hyalinata (Hymenoptera: Apidae) - Silva, Isabel Moreira da; Zanuncio, Jose Cola; Brugger, Bruno Pandelo; Soares, Marcus Alvarenga; Vinha Zanuncio, Antonio Jose; Wilcken, Carlos Frederico [UNESP]; Tavares, Wagner de Souza; Serrao, Jose Eduardo; Sediyama, Carlos Sigueyuki (Nature Publishing Group, 2020)
The toxicity of essential oils that can be used in insect pest management to pollinators needs further studies. Apis mellifera Linnaeus and Trigona hyalinata (Lepeletier) (Hymenoptera: Apidae) foragers were exposed by three pathways to ginger, mint, oregano and thyme essential oils to provide their LC50, LD50 and LC90, LD90. Oregano and thyme were more toxic through contact and topically for A. mellifera while the toxicity of mint and ginger was lower. Trigona hyalinata was more tolerant to the essential oils than A. mellifera. In the walking test, the area was treated (totally or partially) with sub-doses (LC50) obtained via contact. The area fully treated with oregano reduced the distance traveled and the movement speed increased the number of stops by A. mellifera. Similar results were observed for T. hyalinata with oregano and thyme oils. Apis mellifera showed irritability remaining shorter time in the area partially treated with ginger, mint and thyme essential oils while T. hyalinata had similar behavior with ginger and thyme. Essential oils did not repel A. mellifera or T. hyalinata, but those of ginger, mint and thyme reduced the time spent by A. mellifera in areas treated with sublethal doses. Oregano and thyme essential oils reduced the survival, mainly, of A. mellifera, while ginger and mint were selective for both pollinators.